Examining the role of inventory in business enterprises: is there a paradigm shift?. (2016) - Elsayed, Khaled
Empirical evidence regarding the emergence of new inventory role in business enterprises is rare and confined to the work of Chikan (2009, 2011). No further research on the changing role of inventory is surprising given the fact that the sample of Chikan (2009) is small and covers only manufacturing companies. As such, this research contributes to the monological validity of Chikan's inventory new paradigm by replicating and extending his analysis using a sample from Egypt as a less developed country. Although similarities and differences were found between the results of this research and those of Chikan (2009, 2011), the general conclusion is that the findings overall support his argument that a new paradigm of inventory has not only emerged, but also become necessary for the analysis. In short, the new paradigm posits that inventory, as a strategic tool, plays an active role in attaining value creation, flexibility and control.